Implementation of Undercover Buy In The Uncovering Of Narcotics Crimes By BNNK Pelalawan - S, Zulkarnain; M.Sijabat; Ali Ismail Shaleh (Faculty of Law, Universitas Pekalongan, 2024)
Disclosure of narcotics crimes is not easy because drug abuse crimes are carried out in a systematic, organized, and hidden manner. Narcotics transactions are generally conducted at times and places that are difficult for the public to ascertain. Perpetrators always try to evade law enforcement in their drug abuse activities. From its nature, this study falls into observational research conducted through a survey method, which involves direct research at the study location using interview data collection tools. To avoid law enforcement reach, transactions are usually carried out with individuals who are already known due to the rapidity of illegal narcotics circulation. Often, those apprehended by law enforcement are only small-scale perpetrators as dealers, while narcotics traffickers are difficult to trace. Therefore, one strategy employed to uncover such crimes is the use of undercover purchases (Undercoverbuy).